A new standardized methodology for analyzing cartographic information on old maps - Gašperič, Primož (Acta geographica Slovenica, 2023)
This article presents a new methodology for analyzing old maps that was used to identify and interpret cartographic symbols on selected maps. It analyzes fifty-eight maps, originating from the sixteenth to nineteenth centuries and showing the territory of Slovenia. The basic criteria for selecting the maps were authorship, scale, and the territory depicted. The study included maps at a medium scale of 1:200,000 to 1:900,000. Approximately eighty entries were made for each map, and several thousand pieces of data were obtained, which then required a uniform and systematic examination of all cartographic symbols on the maps selected. Before the nineteenth century, changes in symbols for vegetation, relief, transport networks, and explanatory elements were the most evident. The article concludes by highlighting the reliability of cartographic content as a source for research. The new method for examining maps makes it easier to determine the cause-and-effect relationship of cartographic elements to map content.